Improving Digital Branding of Kranggan Tourism Village - Reza Anggriyashati Adara (Linguistic Community Services Journal, 2024)
Digital branding can increase the chances of a tourist attraction becoming known to the public. This event was conducted to provide basic knowledge of digital branding to the stakeholders of tourism village in Kranggan, Bekasi. This research aimed to enhance the digital branding strategies of Kranggan Tourism Village in Bekasi by providing stakeholders with essential knowledge and practical examples. The event was attended by 20 participants. They consisted of civil servants, public citizens and various elements of public who were hoping to improve the quality of tourism village of Kranggan. This event consisted of two stages. The first stage was an introduction of the importance of digital branding toward a tourist attraction. The second stage was a presentation from a content creator about the examples of digital branding conducted by one of clothing brands. This event distributed a survey to monitor the participants' opinions regarding the event." could be "A survey was distributed to gather participants' feedback on the event. The results of the survey showed that most participants thought that the event was beneficial for improving their knowledge of digital branding. Nevertheless, the participants hoped that the examples related to the digital branding strategies could be more extensive. In addition, the participants expected that similar events could be conducted in the near future.